Encyclopedia of optimization - Floudas, Christodoulos A.; Pardalos, P. M. (Panos M.) 1954- (Gale virtual reference library, 2009)
Provides a set of topics that show the spectrum of research and numerous applications that have come from this field. Addresses recent areas where optimization theories and techniques have advanced, particularly in health science and transportation.